Bedside rounds in the hospital environment from the perspective of multiprofessional health teams - Tauana Wazir Mattar e Silva; Marília Alves; Isabela Silva Câncio Velloso; Carolina da Silva Caram; Kateryna Metersky; Rita de Cássia Oliveira (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To analyze the configuration of power relations among the multiprofessional team in the bedside round process in the hospital. Methods: Qualitative research with data analyzed through discourse analysis, based on Michel Foucault's theoretical framework. From September to December 2022, we conducted interviews and field observations with the multiprofessional team at a hospital in Belo Horizonte, Minas Gerais, Brazil, as well as qualitative, semi-structured interviews with 37 professionals. Results: The participants pointed out that the experiences of the professionals involved in bedside rounds depend on how the physician conducts the process, and the physician-centered process makes it difficult for other professionals in the team to participate. Final considerations: The way hospitals organize bedside rounds does not promote knowledge articulation for their professionals. It hinders the circulation of power and harms interdisciplinary work in a process that maintains the physician as the main actor in clinical decisions.